Direct conversion of mouse fibroblasts into osteoblasts and investigating COBRA1 expression responce - Alasar, Walid Almoafy (AUC Knowledge Fountain, 2019)
Fibroblasts are the most common connective tissue cells and are responsible for the synthesis of extracellular matrix (ECM) and collagen. They are mainly of mesenchymal stem cells (MSCs) origin. Fibroblasts are fully differentiated cells although some recent findings reported that fibroblasts possess some potency that allows them to differentiate into other cells types. They are said to undergo adipogenic, chondrogenic, hepatogenic, nurogenic and osteogenic differentiation if grown in the suitable conditions. In the normal physiologic environment, fibroblasts can also differentiate to epithelial cells, a phenomenon known as the mesenchymal epithelial transition (MET). In the current research, we induced L929 mouse fibroblasts to differentiate into osteoblasts cells using the growth media containing Dexamethazone, Ascorbic acid and Beta-Glycerol phosphate which are the substances known to promote osteogenic differentiation. We have increased the concentration of dexamethazone than that used previously, and investigated the effect of this increase on the time of induction. We also investigated the levels of Cobra1 (which is an integral member of the negative elongation (NELF) complex) mRNA in L929 that underwent osteogenic induction compared to the non-induced ones. We show a successful induction the onset of which is earlier than previously reported in the literature. Furthermore, to the best our knowledge our current data, for the first time, suggest a potential role of Cobra1 in maintaining the plasticity of L929.